2019
DOI: 10.1016/j.nucmedbio.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [11C]KB631 as a PET tracer for in vivo visualisation of HDAC6 in B16.F10 melanoma

Abstract: Evaluation of [ 11 C]KB631 as a PET tracer for in vivo visualisation of HDAC6 in B16.F10 melanoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Regarding the development of HDAC6-selective radioligands, Lu et al reported on 11 C-carbonylation methods for labeling tubastatin A, an HDAC6-selective inhibitor (1 in Figure 1), 36 that employed [ 11 C]carbon monoxide. 37 Radiosynthesis of the tubastatin A analog [ 11 C]KB631 ([ 11 C]2 in Figure 1) with [ 11 C]methyl iodide was also reported by Lu et al, 38 and its preclinical evaluation for visualization of B16F10 melanoma has recently been reported by Vermeulen et al 39 Additionally, [ 18 F] Bavarostat was developed by Strebl et al 40 as an adamantane-conjugated HDAC6-selective radioligand. Although [ 18 F]Bavarostat needs a unique rutheniummediated 18 F-deoxyfluorination 41 for its radiosynthesis, its BBB permeability and specific binding in the brain was confirmed by in vivo blocking studies in nonhuman primates.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Regarding the development of HDAC6-selective radioligands, Lu et al reported on 11 C-carbonylation methods for labeling tubastatin A, an HDAC6-selective inhibitor (1 in Figure 1), 36 that employed [ 11 C]carbon monoxide. 37 Radiosynthesis of the tubastatin A analog [ 11 C]KB631 ([ 11 C]2 in Figure 1) with [ 11 C]methyl iodide was also reported by Lu et al, 38 and its preclinical evaluation for visualization of B16F10 melanoma has recently been reported by Vermeulen et al 39 Additionally, [ 18 F] Bavarostat was developed by Strebl et al 40 as an adamantane-conjugated HDAC6-selective radioligand. Although [ 18 F]Bavarostat needs a unique rutheniummediated 18 F-deoxyfluorination 41 for its radiosynthesis, its BBB permeability and specific binding in the brain was confirmed by in vivo blocking studies in nonhuman primates.…”
Section: Introductionmentioning
confidence: 90%
“…Excellent stability of [ 11 C]2 was demonstrated in plasma radio-metabolite analysis in mice 39 ; therefore, the comparison of pharmacokinetics between the radioligands could reveal the influence of structural modifications, such as the introduction of an [ 18 F]fluoroethyl moiety, of [ 18 F]3 on its pharmacokinetics. 38,39 Similarly, brain uptake of [ 18 F]3 was low and stable at around 0.5% ID/g over a 60-minute period. Similarly, in some organs, the radioactivity uptake of [ 18 F]3-injected mice was significantly higher than that observed with [ 11 C]2-injected mice, including the heart, lung, liver, and muscle, at the early time points.…”
Section: Biodistribution In Normal Micementioning
confidence: 99%
See 3 more Smart Citations